واقع الغش الإلكتروني في الامتحانات الجامعية : بحث ميداني بجامعة باتنة 1 - بوتة، نوال (جامعة باتنه 1 - كلية العلوم الإسلامية, 2018)
هدف هذا البحث إلى معرفة واقع الغش الإلكتروني في الامتحانات الجامعية "بحث ميداني بجامعة باتنة 1"، ولتحقيق اهداف هذا البحث تم استخدام المنهج الوصفي التحليلي لملاءمته لأغراض البحث، كما تم استخدام استمارة لجمع البيانات من مجتمع البحث، والتي طبقت بعد حساب صدقها وثباتها على عينة قوامها 960 طالب وطالبة. وقد أظهرت نتائج البحث انتشار الغش الإلكتروني في الامتحانات الجامعية بنسبة معتبرة قدرت ب 48.02 %، كما أظهرت نتائج البحث أهم الوسائل الإلكترونية التي يستخدمها الطالب الجامعي في الغش والمتمثلة في الهاتف الذكي بنسبة 18.54%، سماعات البلوتوث بنسبة 15.10%، الساعات الإلكترونية بنسبة 9.16%، السماعات اللاسلكية بنسبة 5.19%، كما أظهرت نتائج البحث المستويات التي يلجأ إليها الطالب الجامعي في الغش الإلكتروني في الامتحانات الجامعية تمثلت في الاطلاع على المعلومات المدرجة في إحدى وسائل الغش الإلكتروني (الهاتف الذكي-الساعة الإلكترونية ) بنسبة 53.57%، طلب مساعدة من زميل داخل قاعة الامتحان بنسبة 28.85%، الاتصال بزميل خارج قاعة الامتحان بنسبة 17.57%. وفي ضوء نتائج هذا البحث يجدر الاهتمام بهذا الموضوع الحساس بإجراء بحوث أخرى في هذا المجال.
The goal of this research to know the reality of electronic fraud in university examinations &'field research at the University of batna1, to achieve the objectives of this research was the use of the descriptive approach analytical work credited for its suitability for research purposes, as was the use of a form to collect data from the research community, which were applied after the sincerity and constancy of account on a sample of 960 male and female students. And the results of the research showed that the proliferation of electronic fraud in university examinations by considering estimated by 48.02%, the search results also showed the most important electronic means used by the student in the fraud of the smartphone by 18.54%, Bluetooth headset by15.10%, electronic hours by 9.16%, and wireless headphones by 5.10 % The search results also showed levels used by the university student in electronic fraud in university examinations represented the information listed in one of the means of fraud e-mail (Your Smartphone-at electronic commerce) by 53.57%,a request for assistance from a fellow inside the exam hall by 28.85% ,contact a colleague outside the exam hall by 17.57%. The light of the results of this research should be of interest to this sensitive subject to conduct further research in this area.
Keywords: التعليم الجامعي -- الغش في الامتحانات -- الغش الإلكتروني -- جامعة باتنة